Impact Utilization learning mobile in a to learn some basic handball skills - NajiZaidan, Huda; TalalAbdulla, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The handball game is one of the team games that relies on learning basic skills based on the learner’s acquisition of basic motor skills. This is done by investing the available lesson time with an investment that qualifies him to interact with the learning process. Thus, those concerned with the educational process use the mobile learning method, which is characterized by the effectiveness that defines It is the use of small and hand-held portable wireless devices such as mobile phones, personal digital assistants, smart phones, and small personal computers to achieve flexibility and interaction in the two aspects of teaching and learning at any time and anywhere. The researchers found: 1. Using mobile phones as an aid in learning other skills. 2. Using the mobile phone in order for students to obtain information in order to enhance lessons and other events